2020
DOI: 10.1177/0042098019896977
|View full text |Cite
|
Sign up to set email alerts
|

The spatial varying relationship between services of the train network and residential property values in Melbourne, Australia

Abstract: This study investigates the spatial effects of the service frequency and transport interchange facilities of rail stations on residential property values for the entire metropolitan train network in Melbourne. Residential properties are classified as either detached or attached dwellings. Given that a traditional hedonic price model cannot handle the spatial dependence and spatial non-stationarity of the housing market, several geographically weighted regression (GWR) models are used and multicollinearity is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 46 publications
1
12
0
1
Order By: Relevance
“…Similarly, although the distance to bus station is generally negatively correlated to housing price, which may be supported by most studies [6], it also changes over space. Such a phenomenon is consistent with a recent case study in Melbourne [47], which verifies the spatial varying relationship between housing price and transportation facilities. However, the result here further indicates that it has a local spatial effect and is insignificant in most regions.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, although the distance to bus station is generally negatively correlated to housing price, which may be supported by most studies [6], it also changes over space. Such a phenomenon is consistent with a recent case study in Melbourne [47], which verifies the spatial varying relationship between housing price and transportation facilities. However, the result here further indicates that it has a local spatial effect and is insignificant in most regions.…”
Section: Discussionsupporting
confidence: 90%
“…Urban rail transit was found to have a great impact on real estate. In many cases, it was found that rail transit station proximity had a positive impact on residential property value, such as in Shanghai [20], Kuala Lumpur [21], Bangkok [6,[22][23][24], Portland [25], Buffalo [26], London [27], Hamburg [28], Lisbon [29], Melbourne [30], etc. However, in some cities the impact was not spatially even across the city, i.e., being positive and negative in different areas, such as reported in San Diego [31], Tyne and Wear region [32], Ottawa [33], etc.…”
Section: Property Value Upliftmentioning
confidence: 99%
“…The dependent variable, which is the property value, could be the listing price of the property [29,32], the assessed property value [38], or the actual transaction price [21,[39][40][41][42][43]. The price in different years would be adjusted for inflation and other external factors [30]. The value of the property price may be considered as the total price [24,25,27,28,33,36,37,[43][44][45][46] or the price per unit area, i.e., price per square foot or per square meter of the area [6,20,22,23,26,31,34,35,39,[47][48][49][50][51][52].…”
Section: Hedonic Pricing Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…P a d a praktiknya terdapat dua kelompok besar terkait model penelitian. Kelompok pertama adalah kelompok yang menggunakan data sekunder atau data pasar aktual seperti harga transaksi atau harga sewa dari pihak ketiga (Hamidi, Bonakdar, Keshavarzi, & Ewing, 2020;Kauko, 2003), faktor lokasi yang didapat dari pihak ke tiga (Rahadi et al, 2020), informasi iklim (Hino & Burke, 2020) atau data jaringan transportasi dari otoritas terkait (Li, Wang, Callanan, Lu, & Guo, 2020). Kelompok kedua adalah kelompok yang menggunakan data primer yang diperoleh dari kuesioner atau wawancara (Abidoye & Chan, 2016;Babawale & Omirin, 2012;Kauko, 2003;Strand & Vågnes, 2001).…”
Section: Latar Belakangunclassified